RAISING KNOWLEDGE OF STUNTING IN PAYARAMAN REGENCY VIA COMMUNITY EDUCATION AND SUPPLEMENTAL FOODS - Ahmad Ghiffari; Sahrul Wildan; Aisyah Fadhilah Kurnia; Louwen Sandi; Nabila Nurul Fatihah; Rizky Andelina; Aqila Meisya Putri Mulya Nurfauza; Muhammad Wahyu Hidayat; Tasya Julia Dwitania (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2026)
Introduction: Stunting is a chronic condition characterized by impaired linear growth, cognitive deficits and long‑term economic consequences. South Sumatra reports one of the highest stunting burdens in Indonesia. This activity aimed to improve participants’ knowledge of stunting prevention and to monitor changes after educational and supplementary feeding activities. Methods: This community service was conducted during the 63rd Student Study Service (Kuliah Kerja Nyata/KKN) of Universitas Muhammadiyah Palembang in July 2025 in four villages of Payaraman District, Ogan Ilir Regency, South Sumatra. Pregnant women and mothers of infants and toddlers were recruited via local health posts and community leaders. Activities included didactic sessions explaining the definition, causes and prevention of stunting; distribution of high‑protein mung bean porridge fortified with moringa leaf; vitamin A supplementation; and pre‑ and post‑intervention questionnaires to assess knowledge. Results: A total of 98 participants attended the programme. Pre‑ and post‑tests were conducted in Payaraman Timur and Payaraman Barat. In Payaraman Timur, correct responses increased from 8 of 16 (50 %) at baseline to 13 of 16 (81.25 %) after the intervention, representing a 31.25 % improvement in knowledge. In Payaraman Barat, the post‑test showed that 24 of 29 participants (82.8 %) answered correctly. Qualitative feedback indicated that participants better understood the importance of adequate nutrition during the first thousand days of life and the role of hygiene and infection prevention in reducing stunting. Conclusion: The community education and supplementary feeding programme enhanced participants’ understanding of stunting prevention, as reflected by the marked increase in correct responses in Payaraman Timur. Future programmes should include pre‑ and post‑tests in all locations and monitor long‑term anthropometric outcomes to assess the impact on child growth. KEYWORDS community service; nutrition education; stunting; supplementary feeding; student study service